TRANSLATION TECHNIQUES IN INDONESIAN TRANSLATION OF DIALOGUES IN AQUA MAN AND THE LOST KINGDOM MOVIE - Ningsih, Ratna; Pratama , Mochamad Rizqi Adhi (Universitas Ngudi Waluyo, 2024)
This research is aimed at analyzing the translation techniques of English to Indonesian subtitles in the movie entitled Aqua Man and The Lost Kingdom. The theory used in the study was proposed by Molina and Albir (2002), while the method used in this study was a descriptive qualitative method. The total number of data found was 354 and the percentage of each technique are, (1) literal translation occurs 133 times and represents 25%, (2) reduction occurs 75 times and 14%, (3) generalization occurs 64 times and represents 12%, (4) established equivalent occurs 46 times and represents 8,61%, (5) linguistic compression occurs 38 times and represents 7,12%, (6) adaptation occurs 34 times and represents 6,37%, (7) modulation occurs 31 times and represents 5,81%, (8) transposition occurs 27 times and represents 5,06%, (9) particularization occurs 22 times and represents 4,12%, (10) borrowing occurs 20 times and represents 3,75%, (11) discursive creation occurs 15 times and represents 2,81%, (12) compensation occurs 12 times and represents 2,25%, (13) variation occurs 7 times and represents 1,31%, (14) linguistic amplification occurs 6 times and represents 1,12%, and (15) amplification occurs 4 times and represents 0,75%. The most dominant translation technique found in the movie entitled Aqua Man and The Lost Kingdom is literal translation. Keywords: Translation Techniques, Movie Subtitle, Aqua Man and The Lost Kingdom